Electron-hole trapping centers in Na2SO4 with a transition metal impurity Mn - Nurakhmetov, T; Alibay, T.T.; Pazylbek, S.; Zhunusbekov, A.M.; Sadykova, B.M.; Tolekov, D.A.; Shamieva, R.K.; Nurpeissov, A.S. (Eurasian Journal of Physics and Functional Materials, 2026)
The Na2SO4 samples were obtained by slow evaporation method. The mechanisms of the formation of electron and hole trapping centers are investigated by spectroscopic methods. Intrinsic recombination emission of 2.9–3.1 eV and impurity emission of 1.85 eV are excited at 4.0–4.5 eV. Intrinsic SO3−4−SO−4 and impurity Mn+ − SO−4 trapping centers were revealed. The local levels corresponding between the electron and hole trapping center are 4.0–4.5 eV. The decay of intrinsic and impurity trapping centers was recorded at temperatures of 130–150 K and 280–350 K.Recommended CitationNurakhmetov, T.N.; Alibay, T.T.; Pazylbek, S.; Zhunusbekov, A.M.; Sadykova, B.M.; Tolekov, D.A.; Shamieva, R.K.; and Nurpeissov, A.S. (2023) "Electron-hole trapping centers in Na2SO4 with a transition metal impurity Mn," Eurasian Journal of Physics and Functional Materials: Vol. 7: No. 1, Article 1.DOI: https://doi.org/10.32523/ejpfm.2023070102